How national curricula affect the design and transfer of a teaching-learning sequence between two educational systems: Case studies from Greece and Italy - Italo Testa (American Physical Society, 2020)
This empirical study investigates the main features of curricula and contexts that favor or hinder the process of transfer of a teaching-learning sequence (TLS) from the designers’ original situation to a host one. The specific research questions addressed were (RQ1) what were the changes made during the process of transfer in the new context? (RQ2) What were the similarities or differences between the national curricula and contexts that influenced the process of transfer? To answer our research questions, we chose two TLSs, one about optical properties of materials, the other about thermal conductivity, originally designed by two groups of researchers and experienced teachers in Italy and Greece, respectively. The transfer process was analyzed using the “adaptation and reinvention” model, originally developed for the management knowledge research field, while the construct of “institutional distance” was used to describe the influence of country-specific aspects on the transfer process. Data collected included background documents that describe the principles underlying the TLSs design, the decisions and changes made to the original TLSs by the hosting group, and reports on the TLS implementation in classroom practice in the original and in the host context. Content analysis was used to analyze data. Results show that the similarities between the two national curricula and interactions between the involved groups acted mainly as facilitators of the transfer process.